2005
DOI: 10.1901/jeab.2005.21-04
|View full text |Cite
|
Sign up to set email alerts
|

The Sunk Cost Effect in Pigeons and Humans

Abstract: The sunk cost effect is the increased tendency to persist in an endeavor once an investment of money, effort, or time has been made. To date, humans are the only animal in which this effect has been observed unambiguously. We developed a behavior-analytic model of the sunk cost effect to explore the potential for this behavior in pigeons as well as in humans. Each trial started out with a short expected ratio, but on some trials assumed a longer expected ratio part way through the trial. Subjects had the (usua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

17
166
0
11

Year Published

2006
2006
2017
2017

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 101 publications
(194 citation statements)
references
References 26 publications
17
166
0
11
Order By: Relevance
“…We also removed all studies that examined the sunkcost effect in reaction to time or behavioral investments (Soman 2001;Navarro and Fantino 2009;Otto 2010), without providing an hourly exchange rate or wage, from the data set. In addition, some studies included non-human samples (e.g., Maestripieri and Alleva 1991;Arkes and Ayton 1999;Navarro and Fantino 2005;Macaskill and Hackenberg 2012), which were not considered in our analysis. We also excluded all studies analyzing sunk costs with a strategic purpose (e.g., sunk costs as a market entry barrier; Rosenbaum and Lamort 1992) because our focus is on the effect of sunk costs on individual decision behavior and not on corporate strategy.…”
Section: Literature Searchmentioning
confidence: 99%
“…We also removed all studies that examined the sunkcost effect in reaction to time or behavioral investments (Soman 2001;Navarro and Fantino 2009;Otto 2010), without providing an hourly exchange rate or wage, from the data set. In addition, some studies included non-human samples (e.g., Maestripieri and Alleva 1991;Arkes and Ayton 1999;Navarro and Fantino 2005;Macaskill and Hackenberg 2012), which were not considered in our analysis. We also excluded all studies analyzing sunk costs with a strategic purpose (e.g., sunk costs as a market entry barrier; Rosenbaum and Lamort 1992) because our focus is on the effect of sunk costs on individual decision behavior and not on corporate strategy.…”
Section: Literature Searchmentioning
confidence: 99%
“…More recent research suggests, however, that sunk cost effects can be found in pigeons (Navarro & Fantino, 2005). In a cleverly designed experiment, Navarro and Fantino trained pigeons to peck at a light to receive rewards.…”
Section: Sunk Cost Research With Animalsmentioning
confidence: 99%
“…Professor Fantino eloquently showed the commonalities between basic operant research and theory and foraging theory and behavioral ecology (Abarca, Fantino, & Ito, 1985;Fantino, 1985Fantino, , 1991Fantino & Preston, 1988), sparking a vigorous stream of research that continues to this day, including applications in addictions (Bickel, Giordano, & Badger, 2004) and consumer behavior (Hantula, 2012). His ventures into human judgment and decision-making provide a cogent counterpoint to the ubiquitous Bheuristics and biases^literature, demonstrating how fundamental operant principles can explain decision Berrors^and logical fallacies (Fantino, 1998b;Fantino, Kulik, Stolarz-Fantino, & Wright, 1997;Fantino & Stolarz-Fantino, 2008;Fantino, Stolarz-Fantino, & Navarro, 2003) such as base rate errors (Goodie & Fantino, 1996), the conjunction fallacy (Fantino et al, 1997), and sunk cost (Navarro & Fantino, 2005. In his later years, Professor Fantino focused his behavioral acumen on more applied questions such as how Bmindfulness meditation^can increase false memories (Wilson, Mickes, Stolarz-Fantino, Evrard, & Fantino, 2015) and how a soda tax may backfire (Wilson, Stolarz-Fantino, & Fantino, 2013).…”
Section: In Memoriammentioning
confidence: 99%